A Rune-Inscribed Stone from Birsay, Orkney - Marwick, Hugh (Proceedings of the Society of Antiquaries of Scotland, 1922)
The stone was built into the wall of the ruined chapel so that the inscription could not be seen until the stone was moved. Part of the inscription was transcribed as 'Philippus carved (these) runes', the remainder was indistinct. It is suggested that there are two separate inscriptions which were carved at different times.